Concept of Power Line Communication solution for Mesh DC Micro grid based on CAN protocol - Thanh Kha, Tran; Hamed, Yahoui; Catalot Denis, Genon; Nicolas, Siauve; Nicolas, Fourty (International Journal of Engineering and Technology, 2018)
Recently, technologies related to smart grids have attracted more attention due to increasing the demand for renewable energy. One of the most important foundations of smart grids is commonly communications between energies services demands and responses. Almost all the operations on the grids are based on the communications, such as supervision, protection, and isolation. These operations request different requirements for data transmission. The communication technology needs to have high reliability, low latency, and a minimum throughput to guarantee interaction between elements. To limit wires, power line communication (PLC) is a natural choice to deliver bi-directional data transmission between network components to enable smart controller and management of the grid. This paper proposes a PLC solution as a data transmission method for the mesh type DC microgrid. This solution is designed to take advantage of a robust protocol of automotive network - Control Area Network (CAN). The presented architecture is thus intended to propose a PLC system compatible with CAN-bus to provide a safety protocol for DC microgrid with cost effective approach.
Keywords: PLC; protocol; CAN; safety; Mesh DC microgrid; smart grid.